Cognitive Rehabilitation for Attention and Memory in people with Multiple Sclerosis: study protocol for a randomised controlled trial (CRAMMS) - Lincoln, Nadina B.; das Nair, Roshan; Bradshaw, Lucy; Constantinescu, Cris S.; Drummond, Avril E.R.; Erven, Alexandra; Evans, Amy L.; Fitzsimmons, Deborah; Montgomery, Alan A.; Morgan, Miriam (BioMed Central, 2015)
Background: People with multiple sclerosis have problems with memory and attention. Cognitive rehabilitation is a structured set of therapeutic activities designed to retrain an individual’s memory and other cognitive functions. Cognitive rehabilitation may be provided to teach people strategies to cope with these problems, in order to reduce the impact on everyday life. The effectiveness of cognitive rehabilitation for people with multiple sclerosis has not been established. Methods: This is a multi-centre, randomised controlled trial investigating the clinical and cost-effectiveness of a group-based cognitive rehabilitation programme for attention and memory problems for people with multiple sclerosis. Four hundred people with multiple sclerosis will be randomised from at least four centres. Participants will be eligible if they have memory problems, are 18 to 69 years of age, are able to travel to attend group sessions and give informed consent. Participants will be randomised in a ratio of 6:5 to the group rehabilitation intervention plus usual care or usual care alone. Intervention groups will receive 10 weekly sessions of a manualised cognitive rehabilitation programme. The intervention will include both restitution strategies to retrain impaired attention and memory functions and compensation strategies to enable participants to cope with their cognitive problems. All participants will receive a follow-up questionnaire and an assessment by a research assistant at 6 and 12 months after randomisation. The primary outcome is the Multiple Sclerosis Impact Scale (MSIS) Psychological subscale at 12 months. Secondary outcomes include the Everyday Memory Questionnaire, General Health Questionnaire-30, EQ-5D and a service use questionnaire from participants, and the Everyday Memory Questionnaire-relative version and Carer Strain Index from a relative or friend. The primary analysis will be based on intention to treat. A mixed-model regression analysis of the MSIS Psychological subscale at 12 months will be used to estimate the effect of the group cognitive rehabilitation programme. Discussion: The study will provide evidence regarding the clinical and cost-effectiveness of a group-based cognitive rehabilitation programme for attention and memory problems in people with multiple sclerosis.